2006
DOI: 10.1111/j.1471-0528.2006.00973.x
|View full text |Cite
|
Sign up to set email alerts
|

The central issue? Visceral fat mass is a good marker of insulin resistance and metabolic disturbance in women with polycystic ovary syndrome

Abstract: Objective To establish whether visceral fat mass is the most significant variable correlating with insulin resistance and other metabolic parameters in women with polycystic ovary syndrome (PCOS).Design Prospective cross-sectional trial.Setting Reproductive medicine clinic.Population Forty women with anovulatory PCOS.Methods Measurements were taken at recruitment, and analysis was performed to define correlations between the outcome measures and the explanatory variables.Main outcome measures Visceral and subc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
66
2
11

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(89 citation statements)
references
References 40 publications
10
66
2
11
Order By: Relevance
“…These and other studies have shown that increased abdominal fat is an important determinant of increased cardiovascular and metabolic disease (4,5). Most studies have shown that increased abdominal fat is present not only in the majority of women with PCOS who are obese but also occurs in overweight and normoweight women with the syndrome (1,2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These and other studies have shown that increased abdominal fat is an important determinant of increased cardiovascular and metabolic disease (4,5). Most studies have shown that increased abdominal fat is present not only in the majority of women with PCOS who are obese but also occurs in overweight and normoweight women with the syndrome (1,2).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many studies have focused on fat quantity and distribution in women with polycystic ovary syndrome (PCOS) (1)(2)(3)(4). These and other studies have shown that increased abdominal fat is an important determinant of increased cardiovascular and metabolic disease (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…Não há dúvidas de que mulheres com SOP apresentam elevada prevalência de obesidade central (5,8,(9)(10)(11)13,14). Estudos apontam que 50% a 60% dessas pacientes apresentam obesidade abdominal, independente do IMC (21,22).…”
Section: Discussionunclassified
“…Entre os fatores de risco cardiovascular comuns na SOP, a obesidade central tem merecido destacada atenção (5,(8)(9)(10)(11)(12)(13)(14), em virtude do fato de que a distribuição visceral de gordura está relacionada com a RI (13,14), aspecto intimamente associado à fisiopatologia da SOP (15). Além disso, parece não haver dúvidas quanto à relação entre marcadores de obesidade do tipo androide e fatores de risco relacionados ao sistema cardiovascular nesse subgrupo da população feminina (5,8,11,12,14).…”
unclassified
“…Whereas BMI provides a marker of overall adiposity, WC is a better marker of abdominal adiposity, and is the best correlate of visceral fat mass (12). Higher levels of WC are strongly associated with cardiovascular disease.…”
Section: Use Of Anthropometric Measurements To Classify Adipositymentioning
confidence: 99%